Rupture Dynamics and Seismological Variables in Earthquake - Regmi, Jeevan Regmi (Himalayan Physics, 2017)
The Earthquake results by the movement of tectonic plates. There might be various causes of motion of these plates. Based on type of motion and speed of collision, the nature and strength of earthquake varies. It is difficult to present an unique model of physics to explain the earthquake since the nature and strength significantly varies with time and place. The Himalayan Physics Vol. 6 & 7, April 2017 (96-99)